PENINGKATAN KETERAMPILAN BERBICARA SISWA MENGGUNAKAN PERMAINAN BAHASA KELAS II SEKOLAH DASAR ISLAM NAHDLATUL ULUM - Efendi, Sudi; Marzuki, Marzuki; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to improve speaking skills using language games in class II SDI Nahdlatul Ulum Sungai Kakap. This study used collaborative classroom action research (CAR) with a qualitative approach. Data collection done by the observation and documentation. The results of the study showed that the mean score of teacher’ ability to design the learning process through language games in the first cycle was 2.98. The mean score of the second cycle improved to be 3.22. The mean score of the third cycle also improved to 3.55. The mean score of the teacher’ ability to implement the learning process through language games in the first cycle with was 3.29. The second cycle got 0.16 improvements so that the mean score was 3.45. Then, it got 0,41 improvements from the second cycle so the mean score of the third cycle was 3.86. The mean score of student’ speaking ability through language games in the first cycle was 61.11 categorized as Completely but there were still 6 students who were still incomplete. The second cycle got 7.64 improvements so that the mean score was 68.75 categorized as Completed but there were still 3 students who were still incomplete. Then, it got 18.75 improvements so the mean score of the third cycle was 87.50 categorized as Completed for all the students..Keywords: Speaking Skills, Language Games, SDI Nahdlatul Ulum